ATRIBUTOS DO SOLO EM ÁREAS COM TRÁFEGO CONTROLADO DE MÁQUINAS APÓS O CULTIVO DA SOJA - OLIVEIRA, Débora Cristina Sousa Barros de; SANTOS, Maria Aparecida do Nascimentos dos; GUIMARÃES JUNNYOR, Wellingthon da Silva; SILVA, Fagner Luiz Rodrigues da; MARTINS, Murilo Battistuzzi; FERREIRA, Laura Martins1 (lauramartinsferreira45@gmail.com (ANAIS DO ENIC, 2023)
-